Climate Change And Glacial Retreat In The Himalaya: Implications For Soil And Plant Development - Gurung, Janita; Bajracharya, Roshan M (Kathmandu University Journal of Science, Engineering and Technology, 2012)
While there is abundant literature on Himalayan glaciations and glaciers, including glacier retreat, there is limited information on soil development and plant succession in deglaciated Himalayan terrain. This paper reviews current knowledge on soil development and plant succession in deglaciated environments around the world. Implications of plant succession in deglaciated environments, particularly as Himalayan glaciers shrink due to climate change, are discussed. Understanding the effects of climate change on Himalayan soil and vegetation dynamics is crucial for assessing impacts on mountain livelihoods, as well as for implementing effective conservation strategies. DOI: http://dx.doi.org/10.3126/kuset.v8i1.6055 KUSET 2012; 8(1): 153-163